Exposure to Serial Post-Concussion Neurocognitive Testing Does not Affect Future "Updated" Baseline Neurocognitive Performance in Adolescent Athletes. (26th July 2019) - O'Connor, S; Dean, T; Elbin, R J; Schatz, P
Abstract: Purpose: We investigated a dose response for serial post-concussion neurocognitive testing exposure on updated post-concussion baseline testing performance. Methods: Athletes (13-18 yrs) that completed two, valid baseline neurocognitive testing (ImPACT) sessions approximately 1-3 years apart participated in this study. A sub-sample of athletes that sustained a SRC between baseline sessions were categorized into dose-response groups based on the number of serial, post-concussion neurocognitive tests completed following SRC: ONE (n=76), TWO (n=99), and THREE OR MORE (n=111). Athletes that did not sustain a SRC comprised the ZERO group (n=289). Change scores between the first to the second baseline were calculated for the ImPACT Composite and Symptom Scores and compared between the dose-response groups and controls with 5 ANOVAs, with a Bonferroni-corrected p-value of (p<.01). Baseline testing was administered using ImPACT stimuli within the "Baseline" administration, and all post-concussion ImPACT testing was administered using alternate-form associated with that specific post-injury assessment (Post-Injury1, Post-Injury2, etc). Results: ANOVAs revealed no effect of number of post-concussion assessments (0, 1, 2, or 3+) on magnitude of the change between first and final baselines, for Verbal Memory (p=.08), Visual Memory (p=.96), Visual Motor Speed (p=.47), Reaction Time (p=.91), or Total Symptom Scores (p=.86). Conclusion: Repeated exposure to neurocognitive testing has revealed improvements in Visual Motor Speed among normal controls, across test-retest intervals of 1-month, 1-year, and 2-years. However, in this study, exposure to post-concussion, serial neurocognitive testing had no effect on future performance on post-concussion baseline neurocognitive testing.